OS02.6.A The TeloDIAG: How telomeric parameters can help in glioma rapid diagnosis and liquid biopsies approaches. (9th September 2021) - Billard, P; Guerriau, C; Carpentier, C; Juillard, F; Grandin, N; Lomonte, P; Kantapareddy, P; Barritault, M; Rimokh, R; Verrelle, P; Maucort-Boulch, D; Figarella-Branger, D; et al.
Abstract: BACKGROUND: The integration of molecular markers into the WHO 2016 classification has clarified the complex diagnosis of gliomas. Among these biomarkers, the TERT promoter mutation and the loss of ATRX (ATRX loss) are mutually exclusive alterations associated with re-activation of telomerase or alternative lengthening of telomeres (ALT), respectively. Strangely, 25% of gliomas display neither or both these alterations, a situation referred to as abnormal telomere maintenance mechanism (aTMM). MATERIAL AND METHODS: To investigate the TMM actually involved in gliomas, the C-circle (CC) assay was adapted to tumor (FFPE and frozen) samples. RESULTS: We constructed a CC-based algorithm able to identify the TMM of 284 gliomas with either TERT or ATRX alteration, with a sensitivity of 100% and a specificity of 97.3%, and succeeded in deciphering the TMM involved in 122 aTMM gliomas. Additionally, the combination of the TMM, the mutational status of the Isocitrate dehydrogenase 1/2 (IDH) gene, and the histological grading was used as base for a new classification: TeloDIAG. Six subtypes are defined in this classification: tOD, tLGA, tGBM_IDHmt, tGBM, and tAIV, corresponding to oligodendroglioma, IDHmt low grade astrocytoma, IDHmt glioblastoma, and IDHwt glioblastoma, respectively, the last class gathers ALT+ IDHwt glioma. The TeloDIAG diagnosis is 99% concordant with the WHO classification for glioma displaying typical molecular characteristics (N=312). It modified the classification of 38% (N=156) discordant tumors, such as IDHwt Astrocytoma, aTMM tumors, or gliomas with unexpected TMM (e.g. TERTwt oligodendroglioma, ATRX loss GBM). Interestingly, 20% (N=69) of TERTwt, ATRXwt, or IDHwt GBM were actually tAIV, which is remarkable as tAIV-glioma patients' survival tended to be longer (21.2 months) than tGBM patients' survival (16.5 months). Importantly, CC in blood sampled from IDHmt astrocytoma patients was detected with a sensitivity of 56% and a specificity of 95% (N = 206). CONCLUSION: In sum, the TeloDIAG is a new, simple, and efficient tool helping in glioma diagnosis and a promising option for liquid biopsy